2006
DOI: 10.1002/hep.21146
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and physiological spectrum of interferon‐alpha induced thyroiditis

Abstract: Interferon-alpha (IFN␣) is a major treatment modality for several malignant and nonmalignant diseases, especially hepatitis C. Prospective studies have shown that up to 15% of patients with hepatitis C receiving IFN␣ develop clinical thyroid disease, and up to 40% were reported to develop thyroid antibodies. Some of these complications may result in discontinuation of interferon therapy. Thus, interferon induced thyroiditis (IIT) is a major clinical problem for patients receiving interferon therapy. IIT can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
169
2
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 99 publications
(192 reference statements)
9
169
2
14
Order By: Relevance
“…The finding of the present study revealed that there was no significant difference regarding the patient's complain from weakness and fatigue between pre and post intervention program; this could be due to patients' believe that fatigue was a sign of disease Enzymes Among Hepatitis C Virus Patients Undergoing Antiviral Treatment Therapy (Sovaldi Medication) progression which as a result contribute to patients' beliefs that weakness and fatigue were uncontrollable and this supported by [32], who stated that; "the cognitive-behavioral theory posits that patients' beliefs about the illness and fatigue and their coping behaviors, rather than objective disease measures, determine the experience and the consequences of fatigue. When patients are aware of having a chronic illness, they interpret sensations (including fatigue) in the context of their knowledge and beliefs about the illness.…”
Section: Discussionsupporting
confidence: 48%
“…The finding of the present study revealed that there was no significant difference regarding the patient's complain from weakness and fatigue between pre and post intervention program; this could be due to patients' believe that fatigue was a sign of disease Enzymes Among Hepatitis C Virus Patients Undergoing Antiviral Treatment Therapy (Sovaldi Medication) progression which as a result contribute to patients' beliefs that weakness and fatigue were uncontrollable and this supported by [32], who stated that; "the cognitive-behavioral theory posits that patients' beliefs about the illness and fatigue and their coping behaviors, rather than objective disease measures, determine the experience and the consequences of fatigue. When patients are aware of having a chronic illness, they interpret sensations (including fatigue) in the context of their knowledge and beliefs about the illness.…”
Section: Discussionsupporting
confidence: 48%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] some small molecule tyrosine kinase inhibitors (tKis) have been shown to cause hypothyroidism related symptoms to a variable extent, which can reduce a patient's quality of life. we review the available data for tKi related thyroid dysfunction and the hypothesized patho physiological mechanisms of this toxicity.…”
mentioning
confidence: 99%
“…interleukin 2 and interferons (iFns) could induce functional thyroid damage in patients affected by melanoma or renal cell carcinoma (rCC), by causing thy roiditis. [12][13][14][15][16] increased levels of thyroid auto antibodies 14,15 or hypothyroidism without autoantibodies 16,17 have been associ ated with improved outcome in patients with competing interests The authors declared no competing interests. reviews (Flt3), colony stimulating factor 1 receptor (CsF1r), ret, Kit, and platelet derived growth factor receptor.…”
mentioning
confidence: 99%
“…However, patients with destructive thyroiditis were also reported to have inhibitory TSHR-Abs [32]. The most prevalent Tabs in our study were TSHR-Abs and the lowest were TPO-Abs.…”
Section: Discussionmentioning
confidence: 40%